2011
DOI: 10.1177/1352458511416836
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of long-term disability in multiple sclerosis

Abstract: Combined EPs allow prediction of long-term disability in small groups of patients with MS. This may have implications for the choice of monitoring methods in clinical trials and for daily practice decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 33 publications
2
51
0
5
Order By: Relevance
“…By contrast, patients with MS typically have milder attacks with good recovery; permanent disability generally occurs later during the secondary progressive phase of the disease. 30 Our results indicated that both the NMO and MS groups benefitted from the rehabilitation program, yet the NMO group obtained greater functional achievements as expressed by the FIM scores. The longer LOS for NMO group is probably a reflection of the rapid deterioration of functional abilities and early loss of independence.…”
Section: Discussionmentioning
confidence: 58%
“…By contrast, patients with MS typically have milder attacks with good recovery; permanent disability generally occurs later during the secondary progressive phase of the disease. 30 Our results indicated that both the NMO and MS groups benefitted from the rehabilitation program, yet the NMO group obtained greater functional achievements as expressed by the FIM scores. The longer LOS for NMO group is probably a reflection of the rapid deterioration of functional abilities and early loss of independence.…”
Section: Discussionmentioning
confidence: 58%
“…Оно отражает блок или замедление проведения. Замедление и асимме-трия ВЦМП у взрослых имеют прогностическое значение [6,10]. В нашем исследовании только в 2 случаях в группе РС зафиксировано замедление ВЦМП по сравнению с медицинской нормой.…”
Section: Discussionunclassified
“…Leocani et al (2006) multimodal evoked potential score comprising MEP and SSEP in a longitudinal study demonstrated a significant positive correlation between baseline combined evoked potential score and likelihood of disease progression over time. More recently, a composite score derived from MEP and VEP latencies has been shown in a prospective study to be predictive of disability over a 20-year followup period in a group of patients with RRMS and SPMS (Schlaeger et al, 2012. The relationship between prognosis and MRI is weaker for PPMS than RRMS (Nijeholt et al, 1998) and in this group of patients a multimodal evoked potential score encompassing VEP, SSEP and MEP was shown to be predictive of disability over a 3-year period .…”
Section: Tms In the Assessment Of Disease Severity And Prognosismentioning
confidence: 95%